Spark joy : an illustrated master class on the art of organizing and tidying up - Kondo, Marie (Ten Speed Press, an imprint of the Crown Publishing Group, a division of Penguin Random House LLC, 2016)
"Tidying expert Marie Kondo's follow-up to her best-selling book, The Life-Changing Magic of Tidying Up, is an illustrated master manual on her renowned KonMari Method with item-specific guidance and step-by-step folding illustrations"--Provided by publisher.